Assessment of treatment-seeking behavior and healthcare utilization in an international cohort of subjects with overactive bladder. (August 2014) - Jimenez-Cidre, Miguel; Costa, Pierre; Ng-Mak, Daisy; Sahai, Arun; Degboe, Arnold; Smith, Christopher Patrick; Tsai, Kathleen; Herschorn, Sender
Abstract Objective: To assess the association between incontinence severity, treatment-seeking behavior, and healthcare resource utilization (HRU) among participants with overactive bladder (OAB) in eight countries. Research design and methods: A cross-sectional online survey of subjects ≥18 years old in Australia, Europe, and North America, who had a past OAB diagnosis and/or experienced ≥1 urinary incontinence (UI) episode in the preceding 12 months, were eligible to participate. Subjects contacted for the survey were primarily from a voluntary medication monitoring registry, MediGuard. Predominantly stress incontinence subjects were excluded. Incontinence severity was assessed by the number of UI episodes over 3 days and grouped as 0 ('dry'), 1–2, 3–4, and ≥5 UI episodes/day. Subject demographics, employment status, comorbidities, treatment-seeking behavior (past OAB diagnosis; spoken to healthcare provider [HCP]), and HRU (diagnostic tests; HCP visits in 6 months before screening) were analyzed by incontinence severity. Results: Overall, 1341 subjects with OAB (mean age 54.5 years; 70.7% female) were surveyed; 20.2%, 47.7%, 18.8%, and 13.3% of subjects reported 0, 1–2, 3–4, and ≥5 UI episodes/day, respectively. Employment status and comorbidities were significantly (p < 0.05) associated with incontinence severity. The two measures of treatment-seeking behavior were significantly (p < 0.05) associated with incontinence severity groups; the proportion of subjects with a past diagnosis of OAB were 35.8%, 44.8%, 52.4%, and 64.0% in the 0, 1–2, 3–4, and ≥5 UI episodes/day groups, respectively; and 59.0%, 63.6%, 65.9%, and 78.1% of subjects in the respective UI severity groups talked to a HCP about their OAB symptoms. Multivariate linear regression analyses showed a positive and consistent association between incontinence severity and HRU; subjects reported a mean of 2.7, 4.1, 4.4, and 7.7 diagnostic tests overall (p < 0.001), and a mean of 1.4, 2.2, 2.7, and 4.0 HCP visits in the 0, 1–2, 3–4, and ≥5 UI episodes/day groups, respectively (p < 0.001). A potential limitation of the study is the cross-sectional survey methodology which limits the ability to draw causal inferences from the results. Additionally, since this is a web-based survey it is possible respondents who have access to/are familiar with technology were more likely to be enrolled. Conclusions: Incontinence severity was positively associated with both treatment-seeking behavior and HRU among subjects with OAB.